A cure for the blues: opsin duplication and subfunctionalization for short-wavelength sensitivity in jewel beetles (Coleoptera: Buprestidae). Issue 1 (December 2016) - Lord, Nathan; Plimpton, Rebecca; Sharkey, Camilla; Suvorov, Anton; Lelito, Jonathan; Willardson, Barry; Bybee, Seth
Abstract Background Arthropods have received much attention as a model for studying opsin evolution in invertebrates. Yet, relatively few studies have investigated the diversity of opsin proteins that underlie spectral sensitivity of the visual pigments within the diverse beetles (Insecta: Coleoptera). Previous work has demonstrated that beetles appear to lack the short-wavelength-sensitive (SWS) opsin class that typically confers sensitivity to the "blue" region of the light spectrum. However, this is contrary to established physiological data in a number of Coleoptera. To explore potential adaptations at the molecular level that may compensate for the loss of the SWS opsin, we carried out an exploration of the opsin proteins within a group of beetles (Buprestidae) where short-wave sensitivity has been demonstrated. RNA-seq data were generated to identify opsin proteins from nine taxa comprising six buprestid species (including three male/female pairs) across four subfamilies. Structural analyses of recovered opsins were conducted and compared to opsin sequences in other insects across the main opsin classes—ultraviolet, short-wavelength, and long-wavelength. Results All nine buprestids were found to express two opsin copies in each of the ultraviolet and long-wavelength classes, contrary to the single copies recovered in all other molecular studies of adult beetle opsin expression. No SWS opsin class was recovered. Furthermore, the maleAgrilus planipennis (emerald ash borer—EAB) expressed a third LWS opsin at low levels that is presumed to be a larval copy. Subsequent homology and structural analyses identified multiple amino acid substitutions in the UVS and LWS copies that could confer short-wavelength sensitivity. Conclusions This work is the first to compare expressed opsin genes against known electrophysiological data that demonstrate multiple peak sensitivities in Coleoptera. We report the first instance of opsin duplication in adult beetles, which occurs in both the UVS and LWS opsin classes. Through structural comparisons of known insect opsins, we suggest that opsin duplication and amino acid variation within the chromophore binding pocket explains sensitivity in the short-wavelength portion of the visible light spectrum in these species. These findings are the first to reveal molecular complexity of the color vision system within beetles.